Cytomegalovirus (CMV) Shedding in French Day-Care Centers: A Nationwide Study of Epidemiology, Risk Factors, Centers' Practices, and Parents' Awareness of CMV. (18th February 2020) - Alain, Sophie; Garnier-Geoffroy, Françoise; Labrunie, Anaïs; Montané, Amélie; Marin, Benoit; Gatet, Martine; Grosjean, Jérôme; Dufour, Véronique; Saugeras, Mathilde; Postil, Deborah; Hantz, Sébastien
Abstract: Background: Congenital cytomegalovirus (CMV) remains an important healthcare burden, resulting from primary or secondary infection in pregnant women. Exposure to young children's saliva is a major risk factor, as prevalence of CMV shedding can reach 34%. Methods: This cross-sectional, multicenter, nationwide study was conducted in randomly selected day care centers (DCCs), and complemented with a survey among parents and DCCs. All children aged >3 months were eligible. The study measured the CMV shedding prevalence in children's saliva and described CMV genotypes epidemiology. The risk factors for CMV shedding and high viral load were evaluated using multivariable models. Results: A total of 93 DCCs participated. Among the 1770 enrolled children with evaluable samples, the CMV shedding prevalence was 40% (713/1770, 95% confidence interval, 34.6–46.1), independently associated with children aged between 12 and 18 months, history of CMV infection in ≥1 parents, a mid-level income. Prevalence increased with DCC staff workload and attending children number. Viral load was ≥5 log-copies CMV/mL in 48% (342/713). Risk factors for higher viral load included children aged between 12 and 18 months, and still being breastfed. The most frequent genotype combinations were gB1-gN4c-gH2 (6.9%), gB1-gN2-gH2 (6.3%), gB4a-gN3a-gH1 (6.3%), and gB1-gN3b-gH2 (5, 7%). CMV awareness was low in parents: their serological status was unknown by 72% of mothers and 82% of fathers. Only 41% knew something about CMV. Conclusions: CMV shedding was independently associated with risk factors related to the children, family and DCC. Some of these risk factors may influence prevention strategies, including through an improved information provided to parents. Clinical Trials Registration: NCT01704222. Abstract : In this nationwide study, cytomegalovirus (CMV) shedding in children's saliva reached 40% in those attending day-care centers (DCCs). Risk factors for CMV shedding and high viral load were related to the children, parents, and DCCs. Knowledge of these risk factors may orient prevention strategies.